Driving Factors for Students Choosing Fully Online Universities in Indonesia - Suhariyanto, Joko; Efendi, Suryono; Lestari, Rahayu (International Review of Management and Marketing, 2026)
This study investigates the impact of digital transformation on students’ purchasing decision-making in a fully online educational context, emphasizing system quality, information quality, and electronic interface quality. It evaluates the mediating function of digital change and the moderating influence of ease of use. This study uses a national sample from three fully online universities in Indonesia, based on data collected from 290 students. It applies regression analysis involving 13 hypotheses. The Sobel test was used to evaluate mediation hypotheses while the Ping test was used to assess moderation hypotheses. The findings show that successful digital transformation is positively supported by the quality of electronic services and information. System quality surprisingly has a detrimental impact on change, perhaps as a result of structural stiffness or organizational inertia. System quality is a crucial requirement that affects students’ transaction intensity when it comes to purchasing selections. However, because they are seen as minimal service standards, information and service quality do not have a major direct impact. By converting technological capability into purchasing decisions, digital transformation serves a crucial mediating role. Furthermore, by lessening the detrimental effects of information complexity and enhancing purchase motivation through intuitive engagement, ease of use considerably moderates this association.